Epistemological Evolution and Strategic Reorientation of the Journal Puriq Toward Agricultural Sciences - adminUNAH, adminUNAH (2026)
PURIQ Journal begins a new editorial stage focused exclusively on Agricultural Sciences, responding to current challenges related to climate change, sustainability, and global food security. After a trajectory dedicated to Social Sciences, this reorientation represents an academic evolution aimed at strengthening applied and interdisciplinary research in strategic areas such as agronomy, forestry, agroindustry, and agribusiness. The editorial highlights the journal’s commitment to generating and disseminating scientific knowledge that contributes to the sustainable development of agri-food systems. It also recognizes the contributions of the academic community that supported PURIQ’s first stage and invites national and international researchers to join this new scientific vision.